Quercus pseudosetulosa, a new species of Quercus sect. Ilex (Fagaceae) from Dawanshan Island, Guangdong, China - Li, Qiansheng; Li, Shengchun; Lin, Duoqing; Shao, Wen; Tu, Tieyao (Phytotaxa, 2018)
A new species of Quercus (Fagaceae), Q. pseudosetulosa is described and illustrated from Dawanshan Island in Guangdong, China. The new species belongs to the Q. setulosa morpho-complex with glabrous leaf abaxial surface and acuminate tip, but it differs from other related species by its leaf with long petioles, large, thickly leathery, glabrous, the irregular spaced secondary veins, the inconspicuous tertiary veins and the recurved leaf blades. Its distribution, habitats and conservation status are also addressed.